In-car concepts to support working parents - Eardley, Rachel; Hyams, Jenny; Sellen, Abigail (Extended abstracts, proceedings of CHI 2004, 2004)
Working parents are an interesting segment of the population because they have heavy demands in both home and work spheres. In an initial, in-depth study [1], we discovered many different strategies that working parents employ to help them cope with work and family demands whether they are at work, at home or mobile. This research also highlighted working parents’ heavy dependency on the car as a kind of “mobile habitat” in which work and home demands are dealt with. More particularly, we found that the car is the context within which the transition both geographically and mentally between work and home life is managed. Because of this, working parents spoke of a number of particular stresses associated with car travel. Our goal in this strand of the research was to explore new opportunities to support working parents through the development of in-car applications aimed specifically at their needs. There is very little in the published literature aimed at the design of in-car applications focused on a particular population segment (although, see [4]). Most of the work in HCI and Human Factors Engineering is concerned with either driver support or “infotainment” applications (e.g, [2]).